Preoperative dental screening prior to cardiac valve surgery and 90‐day postoperative mortality. Issue 11 (16th August 2020) - Rao, Naman R.; Treister, Nathaniel; Axtell, Andrea; Muhlbauer, Jillian; He, Puhan; Lau, Agnes; Icyda, Ross; Heng, Elbert; Rinewalt, Daniel; McGurk, Siobhan; Kennedy, Kevin; Kaneko, Tsuyoshi; et al.
Abstract: Background: Preoperative dental screening before cardiac valve surgery is widely accepted but its required scope remains unclear. This study evaluates two preoperative dental screening (PDS) approaches, a focused approach (FocA) and a comprehensive approach (CompA), to compare postsurgical 90‐day mortality. Methods: Retrospective cohort analysis was performed on all patients who underwent valve surgery at Brigham and Women's Hospital with FocA and Massachusetts General Hospital with CompA of PDS approach from January 2009 to December 2016. Patients with intravenous drug abuse and systemic infections were excluded. Univariate, multivariable, and subgroup analysis was performed. Results: A total of 1835 patients were included in the study. With FocA 96% of patients (1097/1143) received dental clearance in a single encounter with 3.3% receiving radiographs and undergoing dental extractions. With CompA 35.5% of patients (245/692) received dental clearance in a single encounter, 94.2% received radiographs, and 21.8% underwent dental extractions. There was no significant difference in 90‐day mortality when comparing both PDS approach (10% vs 8.4%, P  = .257). This remained unchanged in a multivariable model after adjusting for risk factors (odds ratio:1.32 [95%CI:0.91‐1.93] [ P  = .14]). Reoperation due to infection was less in FocA (0.5%) vs CompA (2.6) ( P  < .001) and postoperative septicemia was increased in the FocA (1.7%) cohort when compared to the CompA (0.7%) ( P  < .001) patients. Conclusions: There was no difference in post valve surgery 90‐day mortality between patients who underwent a FocA vs CompA of PDS.